Evaluation of the Adaptation of 66 – 72 Month Old Children to Primary Schools in Turkey - Kildan, A. Oğuzhan; Ahi, Berat (Elsevier BV, 2014)
AbstractThe main objective of this study is to determine the views of first grade primary school teachers regarding how 66 to 72 month- old children adapt to school. The working group of this study consists of 25 classroom teachers who work at first grade schools and who have 66 to 72 month-old children in their classes. Personal information form (a) and Interview form (b) were used to gather information during the study. In addition to using a “descriptive analysis” of qualitative research methods, the frequency of the teachers’ responses has been expressed numerically and interpreted. During interviews with the teachers, it was determined that some developmental delays (in terms of dexterity disabilities, difficulties in learning, and so on) were observed in children who began primary school between the ages of 66 to 72 months, compared to other children. In addition, these children experienced difficulties in controlling their toileting and adapting to their school. Teachers pointed out that if children attended nurseries or preschool, developmental differences among children could be eliminated.
Keywords: teachers’ opinions; Adjusment to school; reform in education; 4. Education